Congenital external auditory canal atresia and methods of rehabilitation - Perényi, Ádám; Nagy, Attila; Kiss, József Géza; Rovó, László (Acta Biologica Szegediensis, 2015)
Congenital external auditory canal atresia is a disorder with a prevalence of one in 10 000-20 000 live births and is bilateral in one third of the patients. With a conductive hearing loss of 60 dB, even unilateral atresia restricts hearing related social skills. The degree of middle ear deformity may make reconstruction surgery impossible or too hazardous, thus bone-conduction hearing aids have become the first-line therapy. Children with unilateral cartilaginous and bony external auditory canal atresia were enrolled. High-resolution computed tomography with three dimensional reconstructions were made. Reconstruction surgery from retroauricular approach comprised maximal enlargement of the tympanic and mastoid cavities and their closure with adapted conchal cartilage. Hearing improvement reached the level above the social threshold. The auditory canal remained stable and widely patent and facial nerve function was unremarkable. The authors highlight that surgical reconstruction of the external auditory canal is possible in selected cases. The procedure is safe and effective with a reasonably short surgical time, if it is supported by deep anatomical knowledge, careful preoperative imaging and intraoperative facial nerve monitoring. Stable audiological benefits improve patients’ satisfaction and quality of life. If reconstruction surgery is not possible, bone-conduction hearing aids are beneficial.